Green Dentistry: Sustainable Practices and Materials for a Healthier Planet - Sakchhi, Surabhi; Elbanna, Latifa; Chakor, Manjiri; Nikferjam, Ahmad Zobair; Saeedi, Najibullah; Badve, Sonali; Singh, Sandeep (International Journal of Dental Materials, 2025)
Climate change and environmental degradation have heightened the urgency for sustainable practices across healthcare sectors, including dentistry. Green dentistry, also known as eco-friendly dentistry, aims to integrate dental care with principles of sustainability by utilising resources responsibly, reducing waste, employing eco-friendly materials, and designing clinics with an environmentally conscious approach. This narrative review examines the key domains of sustainable dental practice, including the adoption of bio-based and biodegradable dental materials, low-carbon ceramics and composites, and innovative waste-to-resource approaches, such as hydroxyapatite derived from by-products. Effective waste management strategies, such as reducing single-use plastics, using amalgam separators, and ensuring safe disposal of chemical and infectious waste, are highlighted as essential measures. Digital technologies, including CAD/CAM systems, teledentistry, and electronic health records, further contribute to reducing material waste, paper use, and travel-related emissions. Energy and water saving measures, such as energy-efficient equipment, solar-powered clinics, and water recycling systems, offer additional opportunities to minimize environmental impact. By embracing eco-friendly innovations, dentistry can reduce its ecological footprint while maintaining high standards of patient care, contributing meaningfully to global sustainability goals.